2020
DOI: 10.2147/iprp.s261320
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Medicine-Use Pattern Using World Health Organization’s Core Drug-Use Indicators and Completeness of Prescription at University of Gondar Comprehensive Specialized Hospital, Gondar, Ethiopia: Cross-Sectional Study</p>

Abstract: Background Rational use of medicines is patients receiving medicines appropriate to their diagnosis in doses that meet their requirements for an adequate period of time at an affordable price. Irrational prescribing practices result in ineffective, unsafe treatment, prolong prognosis, and increase health-care costs, and this is a common phenomenon in Ethiopia. The aim of this study was to evaluate medicine-use pattern using World Health Organization core drug-use indicators and completeness of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…As well, eight studies used prescription review, nine studies used prescription review and face to face interview, two studies used observation and face to face interview, and two studies used prescription and drug list review. Concerning geographic distribution, seven studies were conducted from Amhara region, 23 , 27 , 28 , 31–34 six were from Oromia region, 24 , 26 , 35–38 four were from Southern Nations Nationalities and People’s Region (SNNPR), 39–42 one was from Tigray region, 43 one was from Somali region, 25 one was from Harari region, 44 and the remaining one was conducted from three regions of the country (Somali, Harari and Dire Dawa), 45 There is no study that was conducted in Gambela, Benishangul and Afar regions, and Addis Ababa city administration ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As well, eight studies used prescription review, nine studies used prescription review and face to face interview, two studies used observation and face to face interview, and two studies used prescription and drug list review. Concerning geographic distribution, seven studies were conducted from Amhara region, 23 , 27 , 28 , 31–34 six were from Oromia region, 24 , 26 , 35–38 four were from Southern Nations Nationalities and People’s Region (SNNPR), 39–42 one was from Tigray region, 43 one was from Somali region, 25 one was from Harari region, 44 and the remaining one was conducted from three regions of the country (Somali, Harari and Dire Dawa), 45 There is no study that was conducted in Gambela, Benishangul and Afar regions, and Addis Ababa city administration ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In Ethiopia, several fragmented studies have been conducted to investigate the practice of rational drug use in health care facilities using WHO drug use indicators. [23][24][25][26][27][28] However, the studies showed a difference in practice of rational drug use, and to the authors knowledge, the literatures have not been examined systematically. Therefore, this systematic review was aimed to investigate the practice of rational drug use in health care facilities using WHO drug use indicators in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of drugs per encounter, 1.95, is acceptable when compared with WHO standard (1.6-1.8) derived as ideal scenario and with other research results. 3,18,30,31 This result is lower when compared with studies conducted in Eastern Ethiopia, 32 and Arba Minch General Hospital. 12 But this result is higher comparatively with studies conducted at Tibebe-Ghion Comprehensive Specialized Hospital (TGCSH), 25 Dessie Referral Hospital, 33 and two district Hospitals in Northwest Ethiopia.…”
Section: Discussionmentioning
confidence: 68%
“…The World Health Organisation (WHO) reports indicate that more than half of all drugs are prescribed and issued inappropriately (Garg et al, 2014 ). Consequently, this leads to irrational use of drugs, stock-outs, expiries, inefficient use of financial resources, treatment failure and antimicrobial resistance (Action Programme on Essential Drugs and Vaccines, 2010 ; Alex, 2018 ; Chem et al, 2018 ; Getahun et al, 2020 ; Ofori-Asenso & Agyeman, 2016 ; World Health Organization, 2023 ); and patients and the community suffer economic burden prompted by the use of costly medicines (UBOS-Statistical Abstract, 2020 ).…”
Section: Introductionmentioning
confidence: 99%